Effects of Pandemic-Related School Closures on Pupils' Performance and Learning in Selected Countries: A Rapid Review - Klaus Zierer (MDPI AG, 2021)
The coronavirus pandemic has led to drastic measures around the world, which have also affected the education system. Schools were closed in the spring of 2020 in almost every country in the world, and many children and young people are still involved in distance learning to this day. What effect these measures have on children's and young people's learning performance is important in view of the time pressure under which educational policy decisions have to be taken. The rapid review presented in this paper delivers evidence on the effects of school closures to contain the coronavirus pandemic in the spring of 2020 on children's and young people's learning performance in five countries (USA, Belgium, the Netherlands, Switzerland and Germany).